PEMANFAATAN TEPUNG JAGUNG DAN TEPUNG TEMPE DALAM PEMBUATAN KERUPUK - Mustakim ' '; Yusmarini ' '; Netti ' Herawati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine the effects of adding corn flour and tempe flour into crackers. An experimental study was conducted by using a completely randomized design (CRD) with 5 treatments and 3 repetitions. The treatments in this study include JT0 (Corn flour 100%), JT1 (Corn flour 90% and tempe flour 10%), JT2 (Corn flour 80% and tempe flour 20%), JT3 (Corn flour 70% and tempe  flour 30% ) and JT4 (Corn flour 60% and 40% tempe flour). The data were analyzed using variance analysis followed by Duncan's New Multiple Range Test (DNMRT) at a rate of 5%. The result of variance analysis indicated that there is no significant influence of ash content but have significant effects on water content before frying, water content after frying, protein content, sensory assessment of color, flavour, taste, crispness and an overall assessment of the crackers. The best treatment in this study was JT1 with water content before frying of 13.68%, water content after frying of 8.40%, protein content of 6.19%, ash content of 2.23% and descriptive sensory assessments of brownish yellow (3.88), tempe flavored (2.92), rather corny and tempe in flavour (3.52), slightly crunchy (2.40) as well as an overall assessment of crackers is 2.99 (liked). Keywords: Crackers, corn flour and  tempe flour